Patho-morphological changes due to rickets in chicks - SINGH, AMARJIT; GREWAL, G S (The Indian Journal of Animal Sciences, 2013)
Ricket was produced by feeding vitamin-D low diet to l-day-old broiler chicks. Ricketic changes developed from day 10 onwards. Chicks showed marked decline in body weight gain. increase in bone to body weight ratio and decrease in bone ash percentage, Biochemical changes revealed decrease in plasma calcium and phosphorus and an incrt ase in alkaline phosphatase activity. Rauiograph of long bones showed poor mineralization, Growth plate of tibio-tarsus showed lengthened proliferating-prehypertropbhied zone (P-PHZ) and in metaphysis an increase in uncalcified bony tissues along with fibroplasia was absolVed. Parathyroid glands were hypertrophied in these chicks.